Cho biểu thức \(P = \frac{{{a^{\frac{1}{3}}}{b^{ -...

Câu hỏi: Cho biểu thức \(P = \frac{{{a^{\frac{1}{3}}}{b^{ - \frac{1}{3}}} - {a^{ - \frac{1}{3}}}{b^{\frac{1}{3}}}}}{{\sqrt[3]{{{a^2}}} - \sqrt[3]{{{b^2}}}}}\). Mệnh đề nào dưới đây đúng?

A. \(P = \frac{1}{{\sqrt[3]{{ab}}}}\).

B. \(P = \sqrt[3]{{ab}}\).

C. \(P = {\left( {ab} \right)^{\frac{2}{3}}}\). 

D. \(P =  - \frac{1}{{\sqrt[3]{{{{\left( {ab} \right)}^2}}}}}\).

Câu hỏi trên thuộc đề trắc nghiệm

Trắc nghiệm Toán 12 Chương 2 Bài 1 Lũy thừa